Enhance the viscosity properties of ball-shaped Carbonyl iron based magnetorheological fluid by adding glass particles - CHEN Bingsan; LAI Xiaobin; LI Chunyu (Functional Materials, 2018)
In this study, the effect of nonmagnetizable glass particles to the viscosity properties of the ball-shaped Carbonyl iron based magnetorheological fluid containing a mixture of magnetizable and nonmagnetizable particles were investigated. Two different MR fluids with different mass fraction of Carbonyl iron and glass particles were tested in the experiments. Experiment results show that the viscosity is greatly improved when the glass particles are added in the magnetorheological fluid. When the added glass particles mass fraction up to 10%, the viscosity is at the highest value under the application of the currents, nearly 7 times larger than MRF-60 without glass particles. MRF-60, MRF-65 two different magnetorheological fluids exhibits similar phenomena. The proper amount of glass particles can enhance the viscosity of the magnetorheological fluid.